2022
DOI: 10.3390/md20030207
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenolic Levels, In Vitro Antioxidant Properties, and Fatty Acid Profile of Two Microalgae, Tetraselmis marina Strain IMA043 and Naviculoid Diatom Strain IMA053, Isolated from the North Adriatic Sea

Abstract: This work studied the potential biotechnological applications of a naviculoid diatom (IMA053) and a green microalga (Tetraselmis marina IMA043) isolated from the North Adriatic Sea. Water, methanol, and dichloromethane (DCM) extracts were prepared from microalgae biomass and evaluated for total phenolic content (TPC) and in vitro antioxidant properties. Biomass was profiled for fatty acid methyl esters (FAME) composition. The DCM extracts had the highest levels of total phenolics, with values of 40.58 and 86.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 81 publications
(117 reference statements)
0
4
0
Order By: Relevance
“…The same was observed in the species C. costatus and C. socialis from this study, where the phenolic content was significantly lower in all experimental groups exposed to nutrient deficiency (P, N and Si) compared to the control group. Previously, a positive correlation between antioxidant activity and TPC was found in microalgae Tetraselmis marina isolated from the northern Adriatic Sea [16]. Interestingly, in nutrient-deprived culture conditions, both TPC and pigments may contribute significantly to antioxidant capacity [17].…”
Section: Total Phenolic Content and Antioxidant Potentialsmentioning
confidence: 92%
“…The same was observed in the species C. costatus and C. socialis from this study, where the phenolic content was significantly lower in all experimental groups exposed to nutrient deficiency (P, N and Si) compared to the control group. Previously, a positive correlation between antioxidant activity and TPC was found in microalgae Tetraselmis marina isolated from the northern Adriatic Sea [16]. Interestingly, in nutrient-deprived culture conditions, both TPC and pigments may contribute significantly to antioxidant capacity [17].…”
Section: Total Phenolic Content and Antioxidant Potentialsmentioning
confidence: 92%
“…Trentin et al (2022) showed that two microalgae, a naviculoid diatom and a green microalga (Tetraselmis marina), are rich in polyphenolic compounds. Thus, all these microalgae can be considered good candidates to serve as sources of these high-value compounds [35].…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…SBL1 and SBL4 methanolic extracts [ 98 ], and the DPPH and NO radical scavenging activity, metal chelating ability, and FRAP values of N. oculata extracts [ 102 ]. In a recent work, phenolic compounds are recognized as the major factor responsible for the ABTS and DPPH radical scavenging activity and the FRAP values of extracts obtained from T. marina IMA043 strain, although the authors suggest that the remaining activity that cannot be explained by the presence of phenols could be ascribed to other molecules present in the extract [ 85 ]. Similar findings had been reported in previous studies that recognized both phenolic compounds and PUFAs as the contributors on the antioxidant activity exerted by extracts from N. oculata [ 69 ], Tetraselmis sp.…”
Section: Bioactivity Of Tetraselmis Sp and ...mentioning
confidence: 99%